Anti-Proliferative, Anti-Angiogenic and Safety Profiles of Novel HDAC Inhibitors for the Treatment of Metastatic Castration-Resistant Prostate Cancer - Zohaib Rana; Sarah Diermeier; Fearghal P. Walsh; Muhammad Hanif; Christian G. Hartinger; Rhonda J. Rosengren (MDPI AG, 2021)
Metastatic castration-resistant prostate cancer (CRPC) has a five-year survival rate of 28%. As histone deacetylases (HDACs) are overexpressed in CRPC, the HDAC inhibitor suberoylanilide hydroxamic acid (SAHA) was trialled in CRPC patients but found to be toxic and inefficacious. Previously, we showed that novel HDAC inhibitors (Jazz90 (N1-hydroxy-N8-(4-(pyridine-2-carbothioamido)phenyl)octanediamide) and Jazz167 ([chlorido(η5-pentamethylcyclopentadieny[1-4](N1-hydroxy-N8-(4-(pyridine-2-carbothioamido-κ2N,S)phenyl)octanediamide)rhodium(III)] chloride) had a higher cancer-to-normal-cell selectivity and superior anti-angiogenic effects in CRPC (PC3) cells than SAHA. Thus, this study aimed to further investigate the efficacy and toxicity of these compounds. HUVEC tube formation assays revealed that Jazz90 and Jazz167 significantly reduced meshes and segment lengths in the range of 55-88 and 43-64%, respectively. However, Jazz90 and Jazz167 did not affect the expression of epithelial-to-mesenchymal transitioning markers E-cadherin and vimentin. Jazz90 and Jazz167 significantly inhibited the growth of PC3 and DU145 spheroids and reduced PC3 spheroid branching. Jazz90 and Jazz167 (25, 50 and 75 mg/kg/day orally for 21 days) were non-toxic in male BALB/c mice. The efficacy and safety of these compounds demonstrate their potential for further in vivo studies in CRPC models.